1981
DOI: 10.1007/bf02074124
|View full text |Cite
|
Sign up to set email alerts
|

Influence of starvation on the larval development ofHyas araneus (Decapoda, Majidae)

Abstract: The influence of starvation on larval development of the spider crab Hyas araneus (L.) was studied in laboratory experiments. No larval stage suffering from continual lack of food had sufficient energy reserves to reach the next instar. Maximal survival times were observed at four different constant temperatures (2 °, 6 °, 12 ° and 18 °C). In general, starvation resistance decreased as temperatures increased: from 72 to 12days in the zoea-1, from 48 to 18 days in the zoea-2, and from 48 to 15 days in the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
0
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(76 citation statements)
references
References 56 publications
8
67
0
1
Order By: Relevance
“…While larvae development of some crustacean species at high latitudes comprises a lecithotrophic phase (Anger et al 2003), Arctic H. araneus larvae depend on food out of the water column for a successful development. Former studies indicated the crucial importance of a sufficient food supply for development and survival of crustacean larvae (Anger and Dawirs 1981;Dawirs 1983). Larvae in the present study were fed ad libitum to guarantee a suitable food supply, which should be consistent with natural food ability as the estimated biomass (dry mass) in Kongsfjorden is relatively high with 8.8 ± 5.1 g m -2 (Hop et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…While larvae development of some crustacean species at high latitudes comprises a lecithotrophic phase (Anger et al 2003), Arctic H. araneus larvae depend on food out of the water column for a successful development. Former studies indicated the crucial importance of a sufficient food supply for development and survival of crustacean larvae (Anger and Dawirs 1981;Dawirs 1983). Larvae in the present study were fed ad libitum to guarantee a suitable food supply, which should be consistent with natural food ability as the estimated biomass (dry mass) in Kongsfjorden is relatively high with 8.8 ± 5.1 g m -2 (Hop et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…1; for more details, cf. Anger & Dawirs 1981, Anger 1987, Staton & Sulkin 1991. In the PRS experiments, the larvae were fed from hatching for 1 to 6 d, followed by continuous starvation (Treatments F1-F6; Fig.…”
Section: Methodsmentioning
confidence: 99%
“…This critical point within larval development represents a threshold where starved and subsequently fed larvae, which still may remain alive for an extended period, cannot recover from previous nutritional stress, and lose their capability to develop further. Anger & Dawirs (1981) first demonstrated the existence of a PNR in decapod crustacean larvae. Moreover, they discovered a 'point-of-reserve-saturation' (PRS), beyond which food uptake is no longer essential for subsequent development and moulting to the following larval stage; this critical point was later found to be identical with the transition between Stages C (intermoult) and D 0 (early premoult) of the moulting cycle, and thus, was renamed 'D 0 threshold' (Anger 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Further, this peak in nutrients, albeit at very low concentrations, could be due to a decrease in phytoplankton (Dugdale, 1967). The decrease in the phytoplankton community affects the zooplankton community (secondary consumers) directly, causing their decline (Costlow and Bookhout, 1959;Anger and Dawirs, 1981;Emmerson, 1984;Anger, 2001). Despite the higher nutrient values found at the Porto de Santo Antônio station, the amounts registered were within the expected values for oligotrophic regions (Assunção et al, 2016).…”
Section: Ecosystem Processes Affecting the Planktonic Decapodsmentioning
confidence: 99%